Facultative CTCF sites moderate mammary super-enhancer activity and regulate juxtaposed gene in non-mammary cells - M. Willi (Nature Portfolio, 2017)
Chromatin neighbourhoods, formed by CTCF, have been proposed to isolate enhancers and their target genes from other regulatory elements. Here, the authors provide evidence that while CTCF binding does regulates mammary-specific super-enhancers, CTCF sites are relatively porous borders.